Implementation of Multicultural Education for Students through Seven Values of Islamic History Education in Indonesia - Munarun, Ahmad; Fatmawati, Nilal Muna; Muthohar, Sofa (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2025)
A study of the representation of multicultural educational values in textbooks is important because textbooks are the primary tool in the process of internalizing values in students. In the context of Indonesia's multicultural society, it is important to ensure that textbooks reflect diversity and encourage inclusive attitudes from an early age. This study aims to uncover the representation of multicultural educational values in Islamic Cultural History textbooks for secondary schools in Indonesia. This study uses a qualitative method with content analysis, and the data sources were taken from fourteen texts in Islamic Cultural History textbooks for Islamic secondary schools written by the Ministry of Religious Affairs of the Republic of Indonesia. All books were analyzed using three approaches, namely text analysis, discursive practice, and social practice analysis, as established by Norman Fairclough. The analysis identified seven main messages reflecting multicultural values, including religious tolerance, cross-ethnic collaboration, open and inclusive governance practices, and respect for local wisdom, ethics-based leadership, cultural mixing, and a critical stance toward corruption. These findings underscore the important role of Islamic secondary school textbooks in shaping inclusive educational practices, while also highlighting the need for a more critical and contextual approach to history in multicultural societies.